Etiological diagnosis in limb reduction defects and the number of affected limbs: A population‐based study in the Northern Netherlands. Issue 12 (21st September 2020) - Bergman, Jorieke E. H.; Löhner, Katharina; van der Sluis, Corry K.; Rump, Patrick; de Walle, Hermien E. K.
Abstract: Limb reduction defects (LRDs) that affect multiple limbs are considered to be more often heritable, but only few studies have substantiated this. We aimed to investigate if an etiological diagnosis (genetic disorder or clinically recognizable disorder) is more likely to be made when multiple limbs are affected compared to when only one limb is affected. We used data from EUROCAT Northern Netherlands and included 391 fetuses and children with LRDs born in 1981–2017. Cases were classified as having a transverse, longitudinal (preaxial/postaxial/central/mixed), intercalary, or complex LRD of one or more limbs and as having an isolated LRD or multiple congenital anomalies (MCA). We calculated the probability of obtaining an etiological diagnosis in cases with multiple affected limbs versus one affected limb using relative risk (RR) scores and Fisher's exact test. We showed that an etiological diagnosis was made three times more often when an LRD occurred in multiple limbs compared to when it occurred in one limb (RR 2.9, 95% CI 2.2–3.8, p < 0.001). No genetic disorders were found in isolated cases with only one affected limb, whereas a genetic disorder was identified in 16% of MCA cases with one affected limb. A clinically recognizable disorder was found in 47% of MCA cases with one affected limb. Genetic counseling rates were similar. We conclude that reduction defects of multiple limbs are indeed more often heritable. Genetic testing seems less useful in isolated cases with one affected limb, but is warranted in MCA cases with one affected limb.